2021
DOI: 10.3390/ijms222312714
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Mitigates Oxidative Stress and Behavioral Impairments Induced by Deltamethrin and Lead Toxicity in Zebrafish

Abstract: Environmental contamination from toxic metals and pesticides is an issue of great concern due to their harmful effects to human health and the ecosystems. In this framework, we assessed the adverse effects when aquatic organisms are exposed to toxicants such as deltamethrin (DM) and lead (Pb), alone or in combination, using zebrafish as a model. Moreover, we likewise evaluated the possible protective effect of vitamin C (VC) supplementation against the combined acute toxic effects of the two toxicants. Juvenil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…The normality and distribution were determined by Shapiro–Wilk test with Graph Pad Prism software (v 9.1.0.221, San Diego, CA, USA). Subsequently, multiple comparisons between the initial behavior and the days of testing within the groups were performed with one-way ANOVA followed by Dunnett’s test [ 21 , 22 ]. Trends were generated using OriginPro software (v 9.3-2016, OriginLab Corporation, Northampton, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The normality and distribution were determined by Shapiro–Wilk test with Graph Pad Prism software (v 9.1.0.221, San Diego, CA, USA). Subsequently, multiple comparisons between the initial behavior and the days of testing within the groups were performed with one-way ANOVA followed by Dunnett’s test [ 21 , 22 ]. Trends were generated using OriginPro software (v 9.3-2016, OriginLab Corporation, Northampton, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…6 Many studies have shown that the antioxidant bioactive substances can protect against Pb exposure-induced toxicity in animal models. 7,8 It was suggested that the combination of chelating agents and antioxidants can better manage Pb toxicity. 9 However, the commonly used chelators in heavy metal treatment can cause serious side effects.…”
Section: Introductionmentioning
confidence: 99%
“…After Cd entered liver cells, it could cause the cells to release pro-inflammatory cytokines (IL-6, TNF-α),and the ROS level in the cells increased sharply, leading to inflammatory damage [ 10 ]. Supplementing antioxidants could intervene in the damage caused by environmental pollutants to animals by improving their antioxidant functions [ 11 , 12 , 13 ], but excessive addition could also cause damage to animals. Generally, Cd can cause damage to cells through a variety of mechanisms such as promoting oxidative stress, inducing apoptosis, triggering DNA damage, interfering with oxidative phosphorylation processes in the mitochondria, and promoting inflammatory responses [ 14 ].…”
Section: Introductionmentioning
confidence: 99%